Detectable Vancomycin Stool Concentrations in Hospitalized Patients with Diarrhea Given Intravenous Vancomycin - Taryn A. Eubank; Chenlin Hu; Anne J. Gonzales-Luna; Kevin W. Garey (MDPI AG, 2023)
Vancomycin is not appreciably passaged via the colonic membrane to the gastrointestinal (GI) tract in persons with an intact gut epithelium due to its large chemical structure. However; hospitalized patients with diarrhea often have a disrupted GI tract. The aim of this study was to determine the frequency of detectable vancomycin concentrations in the stool of patients with antibiotic-associated diarrhea receiving IV vancomycin. This was a multicenter cohort study of hospitalized patients with stool samples collected for Clostridioides difficile testing. Leftover stool samples were collected from patients who had received at least 3 days of IV vancomycin. Fecal vancomycin was quantified by high-performance liquid chromatography. The study cohort included 33 unique patients, majority female (54.5%) aged 60 years (range 23-84). Eighteen of thirty-three patients (54.5%) tested positive for C. difficile toxins. The average duration of systemic vancomycin administration prior to stool collection was 3.5 (range 2-15) days. Three of 33 (9%) stool samples had a detectable vancomycin concentration (range 1.2-13.2 mcg/mL). These concentrations may promote the development of vancomycin-resistant Enterococcus or van mutations in C. difficile, leading to vancomycin resistance. Further studies on implications are warranted.